
Solution:
Taking LHS,
= \sqrt{2 +\sqrt{2+ 2cos 4A}}
[Hint: 4A = 2A +2A]
= \sqrt{2 +\sqrt{2+ 2cos (2A +2A)}}
[Hint: cos 2A = 2cos²A -1]
= \sqrt{2 +\sqrt{2+ 2(2cos² 2A -1)}}
= \sqrt{2 +\sqrt{2+ 4cos² 2A -2}}
[Hint: +2-2 = 0]
= \sqrt{2 +\sqrt{4cos² 2A}}
[Hint: 4cos² 2A = (2cos2A)(2cos2A) so, √(4cos²2A) = 2cos2A]
= \sqrt{2 +2cos 2A}
[Hint: cos2A = 2cos²A -1]
= \sqrt{2 +2(2cos²A -1)}
= \sqrt{2 +4cos²A -2}
= \sqrt{4cos²A}
= 2cos A
= RHS
Here is the Facebook link to the solution of this question in image.
Related Notes:
Link: Introduction To Trigonometry
Link: Values of Trigonometric Ratios
Link: Compound Angles
Question: Prove that: √{2 + √(2 + 2cos 4A)} = 2 cosA | SciPiPupil
#SciPiPupil
#TrigonometricIdentities
#Trigonometry
0 Comments
You can let us know your questions in the comments section as well.